Reduction of fractionated dissolved organic matter in raw water supply by membrane process - Warintorn Banchapattanasakda (Prince of Songkla University Faculty of Engineering (Environmental Engineering), 2013)
Thesis (M.Eng., Environmental Engineering)--Prince of Songkla University, 2011